2022
DOI: 10.3389/fpsyt.2022.947435
|View full text |Cite
|
Sign up to set email alerts
|

Home-based transcranial direct current stimulation in dual active treatments for symptoms of depression and anxiety: A case series

Abstract: Transcranial direct current stimulation (tDCS) is a potential treatment strategy across some psychiatric conditions. However, there is high heterogeneity in tDCS efficacy as a stand-alone treatment. To increase its therapeutic potential, researchers have begun to explore the efficacy of combining tDCS with psychological and pharmacological interventions. The current case series details the effect of 6–10 weeks of self-administered tDCS paired with a behavioral therapy smartphone app (Flow™), on depressive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…2 (sham): travel, loss of interest Changes from baseline to week 2,4, 8 in the BDI-II (primary Outcome), QOLIE-31 and HAM-A score (secondary Outcome), improvement over time but no group difference S: active and sham, monitoring of technical parameters. W: different groups of medications A = yes Q = yes S = yes T = yes V = yes Sobral et al [ 28 ] Case series, open label, combination of home-based tDCS with App based psychological intervention, MDD and/or comorbidities N = 7, 4 female, 26–51 years old; Single condition, active + app-based intervention: one-size-fits-all cap, prefrontal, anode left, cathode right, 2 mA, 30 min, 18 or 21 sessions in 6 weeks Supervised training, self-administered by patients, clinical progress monitoring in person and remotely using Zoom No SAEs, most common AEs: scalp irritation, tingling, itching, and burning sensation. Adherence and acceptability overall high (ACCEPT-tDCS scores), 2 patients missed > 50% tDCS sessions (personal challenges), 1 drop-out (compliance) Changes from baseline to week 6 in: MADRS-Self rating and BDI-II, STAI-Trait clinical improvement in MADRS-S in 5 patients and in STAI-Y2 5 patients S: combination with app-based intervention W: 2 patients initiated CBT at same time as study, no control group A = yes Q = no S = yes T = no V = yes Woodham et al [ 30 ] Open label, single-arm study of home-based tDCS in MDD N = 26, 19 female, 40.9 ± 14.2 years Single condition, active tDCS, F3 anode, F4 cathode, 2 mA, 30 min, 21 sessions in 6 weeks Self-administered, research team member was present in person or by real-time video call at each session No SAEs, most common side effects were skin redness, tingling, itching, mild burning sensation, headache.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (sham): travel, loss of interest Changes from baseline to week 2,4, 8 in the BDI-II (primary Outcome), QOLIE-31 and HAM-A score (secondary Outcome), improvement over time but no group difference S: active and sham, monitoring of technical parameters. W: different groups of medications A = yes Q = yes S = yes T = yes V = yes Sobral et al [ 28 ] Case series, open label, combination of home-based tDCS with App based psychological intervention, MDD and/or comorbidities N = 7, 4 female, 26–51 years old; Single condition, active + app-based intervention: one-size-fits-all cap, prefrontal, anode left, cathode right, 2 mA, 30 min, 18 or 21 sessions in 6 weeks Supervised training, self-administered by patients, clinical progress monitoring in person and remotely using Zoom No SAEs, most common AEs: scalp irritation, tingling, itching, and burning sensation. Adherence and acceptability overall high (ACCEPT-tDCS scores), 2 patients missed > 50% tDCS sessions (personal challenges), 1 drop-out (compliance) Changes from baseline to week 6 in: MADRS-Self rating and BDI-II, STAI-Trait clinical improvement in MADRS-S in 5 patients and in STAI-Y2 5 patients S: combination with app-based intervention W: 2 patients initiated CBT at same time as study, no control group A = yes Q = no S = yes T = no V = yes Woodham et al [ 30 ] Open label, single-arm study of home-based tDCS in MDD N = 26, 19 female, 40.9 ± 14.2 years Single condition, active tDCS, F3 anode, F4 cathode, 2 mA, 30 min, 21 sessions in 6 weeks Self-administered, research team member was present in person or by real-time video call at each session No SAEs, most common side effects were skin redness, tingling, itching, mild burning sensation, headache.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent case series of interventions involving tDCS combined with app-based behavioural therapy reported antidepressant effects, feasibility and safety. [ 27 , 28 ]. Some problems of adherence, with only one patient completing the course per protocol, were also reported by Sobral and colleagues.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in CMHTs typically have severe mental illness and more than one a mental illness diagnosis, and they may need other treatments at the same time as (Sobral et al, 2022;Woodham et al, 2022;Rimmer et al, 2022;Griffiths et al, 2023). Some participants did not use the training modules; autism, ADHD, and unwillingness to try prevented use.…”
Section: Discussionmentioning
confidence: 99%
“…Flow is a product that can be purchased by anyone over the age of 18; it is combined tDCS (delivered by Flow FL-100) and software app-based wellbeing behaviour training (training module titles include: physical exercise, nutrition, mindfulness, sleep, and choosing actions). In a case series study of Flow, reliable change index (RCI) improvements were reported in depressive symptoms in five out of seven patients with depression (Sobral et al, 2022). In a 24-participant open-label single-arm feasibility study, a significant improvement in depressive symptoms after 6 weeks of treatment was reported, which was maintained at 3 and 6 months, and most participants reported that Flow was acceptable and that they would recommend it to others (Woodham et al, 2022).…”
Section: Introductionmentioning
confidence: 97%
“…The commercially available product "Flow", which is combined tDCS (delivered by Flow FL-100) and software app-based well-being behaviour training (exercise, nutrition, mindfulness, sleep, choosing actions), has been subject to investigation. In a case series study, reliable change index (RCI) improvements were reported in depressive symptoms in five out of seven patients with depression (Sobral et al, 2022). In a 24-participant open-label single-arm feasibility study, there was a significant improvement in depressive symptoms after 6 weeks of treatment, which was maintained at 3 and 6 months, with most participants stating that Flow was acceptable and that they would recommend it (Woodham et al, 2022;Rimmer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%